2020
DOI: 10.48550/arxiv.2010.14239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and electronic properties of realistic two-dimensional amorphous topological insulators

Bruno Focassio,
Gabriel R. Schleder,
Marcio Costa
et al.

Abstract: We investigate the structure and electronic spectra properties of two-dimensional amorphous bismuthene structures and show that these systems are topological insulators. We employ a realistic modeling of amorphous geometries together with density functional theory for electronic structure calculations. We investigate the system topological properties throughout the amorphization process and find that the robustness of the topological phase is associated with the spin-orbit coupling strength and size of the pri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Amorphous solids play an important role in condensed matter physics [1]. In the context of topological physics, while topological phases are primarily pursued in crystalline materials with translational symmetry [2][3][4][5][6][7], recent studies showed that topological phases for noninteracting quantum particles can also exist in two or three dimensional amorphous systems [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. From another perspective, amorphous materials can be viewed as a limiting case when structural disorder arising from atom position randomness is included in a crystalline system.…”
mentioning
confidence: 99%
“…Amorphous solids play an important role in condensed matter physics [1]. In the context of topological physics, while topological phases are primarily pursued in crystalline materials with translational symmetry [2][3][4][5][6][7], recent studies showed that topological phases for noninteracting quantum particles can also exist in two or three dimensional amorphous systems [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. From another perspective, amorphous materials can be viewed as a limiting case when structural disorder arising from atom position randomness is included in a crystalline system.…”
mentioning
confidence: 99%
“…Since atoms in amorphous materials are randomly distributed in space, the solids do not respect translational symmetries. While the physics on topological phases of matter is mainly established in crystalline solids with spatial order, it was surprisingly found that topological states can also occur in amorphous solids [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recently, topological phases have been generalized to the higher-order case where (n−m)-dimensional (with 1 < m ≤ n) gapless boundary states happen in an ndimensional system [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
mentioning
confidence: 99%